2021
DOI: 10.1016/j.medj.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin-Mediated Hypoferremia Disrupts Immune Responses to Vaccination and Infection

Abstract: Iron deficiency is very common in humans and animals. Frost et al. demonstrate that low concentrations of iron in serum, caused by the hormone hepcidin, inhibit the body's response to vaccines and infections; conversely, increasing iron can boost immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(131 citation statements)
references
References 61 publications
8
123
0
Order By: Relevance
“…Iron deficient and iron-deficient anaemic children in our study had lower immune response for MSP3 FVO antigen compared to the iron-sufficient and iron-replete study participants after receiving MNP with iron. Other findings suggested that humoral and cell-mediated immunogenic mechanisms were influenced by iron deficiency and iron deficiency anaemia resulting in their poor immunological response [27,31,[35][36][37]. Possibly, the effects of Iron deficient and irondeficient anaemia in children led to impairment on the maturation and proliferation of immune cells especially B and T-lymphocytes, thus increasing their vulnerability to other infections including malaria [31,38].…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficient and iron-deficient anaemic children in our study had lower immune response for MSP3 FVO antigen compared to the iron-sufficient and iron-replete study participants after receiving MNP with iron. Other findings suggested that humoral and cell-mediated immunogenic mechanisms were influenced by iron deficiency and iron deficiency anaemia resulting in their poor immunological response [27,31,[35][36][37]. Possibly, the effects of Iron deficient and irondeficient anaemia in children led to impairment on the maturation and proliferation of immune cells especially B and T-lymphocytes, thus increasing their vulnerability to other infections including malaria [31,38].…”
Section: Discussionmentioning
confidence: 99%
“…Iron levels are key to adaptive responses to pathogens and vaccines; anemia, iron or increased hepcidin and low serum iron caused by a mutation in TMPRSS6 predict reduced responses to rubella, diphtheria, pertussis, H. influenzae type B and pneumococcal vaccines [ 212 , 213 ]. Importantly, in humans another homozygous mutation in TFRC (the gene encoding TFR1) results in defective TFR1 iron internalization.…”
Section: Metals and Adaptive Immune Cells Of The Lungmentioning
confidence: 99%
“…ID in mice attenuates T-cell-dependent and -independent antigenspecific antibody responses, and impairs B-cell proliferation [80]. The intensified metabolism of activated lymphocytes requires high amounts of iron, and T-cell and B-cell responses to adenovirus and vaccinia virus are inhibited in ID mice [81]. Imposing hypoferremia blunts T cell, B cell, and neutralizing antibody responses to influenza virus infection in mice, exacerbating lung inflammation and morbidity, and iron repletion improved the response to vaccination in ID mice [81].…”
Section: Ironmentioning
confidence: 99%
“…The intensified metabolism of activated lymphocytes requires high amounts of iron, and T-cell and B-cell responses to adenovirus and vaccinia virus are inhibited in ID mice [81]. Imposing hypoferremia blunts T cell, B cell, and neutralizing antibody responses to influenza virus infection in mice, exacerbating lung inflammation and morbidity, and iron repletion improved the response to vaccination in ID mice [81]. A recent birth cohort study in Kenya has shown that ID at time of routine infant vaccination is a strong predictor of vaccine response to diphtheria, pertussis and pneumococcus [82].…”
Section: Ironmentioning
confidence: 99%